2012
DOI: 10.1159/000342772
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Hematopoiesis after Iron Chelation Therapy with Deferasirox in Patients with Aplastic Anemia

Abstract: Iron overload due to regular transfusions of packed red cells can cause multiple organ damage. Iron chelation therapy (ICT) is important in patients with aplastic anemia (AA) who require blood transfusions as supportive management. With the introduction of the oral iron chelator deferasirox, ICT has become more widely available and feasible. We studied 4 adult AA patients who had transfusion-induced iron overload and showed hematological improvement after ICT with oral deferasirox. Following deferasirox treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…The patient, however, reported no other drug intake, and we consider this to be further evidence of improved hematopoiesis with ICT leading to sustained transfusion independence as described in several case reports in patients with primary myelofibrosis [2,5,12,13,14,15,18]. Restoration of trilineage hematopoiesis with ICT with deferasirox was also described in several patients with aplastic anemia [12,23,24]. However, no other similar histological improvement in a patient with advanced myelofibrosis, as in the patient described here, has been reported before.…”
Section: Discussionsupporting
confidence: 58%
“…The patient, however, reported no other drug intake, and we consider this to be further evidence of improved hematopoiesis with ICT leading to sustained transfusion independence as described in several case reports in patients with primary myelofibrosis [2,5,12,13,14,15,18]. Restoration of trilineage hematopoiesis with ICT with deferasirox was also described in several patients with aplastic anemia [12,23,24]. However, no other similar histological improvement in a patient with advanced myelofibrosis, as in the patient described here, has been reported before.…”
Section: Discussionsupporting
confidence: 58%
“…In fact, one report demonstrated that iron chelation therapy improved haematopoiesis in transfusiondependent patients with thymoma-associated PRCA, although the mechanism was uncertain (Kojima et al, 2013). A similar effect of iron chelation therapy on haematopoiesis has been described in aplastic anaemia patients (Oliva et al, 2010;Lee et al, 2013).…”
Section: Months Aōer Diagnosis Survivalmentioning
confidence: 89%
“…Obviously, this rationale can be applied only in the context of a well‐designed clinical trial. The initial published experiences in various diseases clearly support larger clinical trials.…”
Section: Management Of Iron Overload During Transplantmentioning
confidence: 81%